2012
DOI: 10.5423/ppj.oa.05.2012.0069
|View full text |Cite
|
Sign up to set email alerts
|

Partial Biological and Molecular Characterization of Tomato yellow fruit ring virus Isolates from Potato

Abstract: Eight potato-producing provinces of Iran were surveyed during the growing seasons of 2004−2006 to detect the presence of Tomato yellow fruit ring virus (TYFRV), a tentative species in the genus Tospovirus. A total of 1,957 potato leaf samples were collected from plants with tospovirus-like symptoms of chlorotic or necrotic spots, chlorosis and necrosis. The samples were tested by enzyme-linked immunosorbent assay using TYFRVspecific antibodies. Among those tested, 498 samples (25.4%) were found to be infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The phylogenetic analyses divided TYRV populations into three clusters corresponding to geographical regions of their origin. The phylogenetic division into two Iranian clusters was reported previously [ 30 , 82 ]. Based on the results obtained by Golnaraghi et al the isolate from Kenya grouped in Iranian cluster 2 [ 30 ].…”
Section: Discussionmentioning
confidence: 85%
“…The phylogenetic analyses divided TYRV populations into three clusters corresponding to geographical regions of their origin. The phylogenetic division into two Iranian clusters was reported previously [ 30 , 82 ]. Based on the results obtained by Golnaraghi et al the isolate from Kenya grouped in Iranian cluster 2 [ 30 ].…”
Section: Discussionmentioning
confidence: 85%
“…In general, it can be said that the overall nucleotide composition is effective on codon usage bias (Jenkins and Holmes 2003). In the study done on Turnip Mosaic Virus (Ohshima et al 2002) and Tomato Yellow Fruit Ring Virus (Pourrahim et al 2012) it was shown that the hosts can play a important role in the evolution of the host-virus. Our nucleotide composition results showed that CaMV coding sequences prefer codons ending in A.…”
Section: Discussion/conclusionmentioning
confidence: 99%